Toxic and nontoxic elemental enrichment in biochar at different production temperatures - Anyika, C.; Majid, Z.A.; Rashid, M.; Isa, A.B.; Ismail, N.; Zakaria, M.P.; Yahya, A. (Elsevier, 2016)
The major impediment to the use of biochar for soil amendment is the presence of toxic elements; however, it is not known how variations in production temperature affect the enrichment behaviour of toxic elements as identified by mass loss and whether the level of nontoxic elements compromises biochar quality. These goals require an understanding of the solid phase which constitutes the tar and ash fractions that harbour majority of the Cation exchange capacity (CEC) and functional groups of biochars and the possible mechanisms through which these metals interact with the solid phase. Results showed that the enrichment behaviour of individual toxic and nontoxic elements at low production temperatures of 350 and 450 °C was significantly different (p < 0.005) to that of high production temperature of 650 °C. The concentration of individual toxic elements revealed maximum enrichment of 193,957 ± 36,881 μg kg-1 and 1650 ± 203 μg kg-1 for Na and B respectively at the 450 °C. While the concentrations of individual nontoxic elements, exhibited maximum enrichment of 665,187 ± 119,715 μg kg-1, 58,335 ± 13,985 μg kg-1, 8858 ± 3574 μg kg-1 and 4907 ± 1174 μg kg-1 for K, Mg, Si and Al respectively at the 450 °C. Conversely, As was the only toxic element that exhibited maximum enrichment of 21 ± 9 μg kg-1, at the 650 °C. Total toxic elemental concentrations indicated strong relationship with percentage mass loss (r2 = 0.998, p < 0.05), which was greatest at 450 °C, but indicated strong negative relationship with percentage ash content (r2 = -0.946, p < 0.210), which was greatest at 650 °C. Therefore, the 650 °C was effective in reducing both the toxic and nontoxic elements in biochar and thus, presented a quality biochar, due to its pi electrons which can result in dual benefits such as stronger binding of inorganic and organic elements to biochar in soils.